2006
DOI: 10.1177/000331970605700314
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and Acute Myocardial Infarction

Abstract: The objective of this paper is to report a case of acute, non-q-wave myocardial infarction, presumably secondary to gemcitabine chemotherapy for nonsmall cell lung cancer. A 43-year-old woman with postpartum cardiomyopathy and ischemic heart disease was treated with gemcitabine for metastatic nonsmall cell lung cancer. Three days after her 5th treatment with gemcitabine, she developed chest pain and was diagnosed as having acute, non-q-wave myocardial infarction. She made an uneventful recovery. An objective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Interestingly, all the patients who developed AMI related to gemcitabine therapy had pre-existing CAD. Two of these patients were already on appropriate antianginal medications before they experienced gemcitabine-related myocardial ischemia [17,18]. In another patient with a previous episode of gemcitabine-induced myocardial ischemia, the next gemcitabine infusion was started concomitantly with IV nitroglycerine and beta blockers [19].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all the patients who developed AMI related to gemcitabine therapy had pre-existing CAD. Two of these patients were already on appropriate antianginal medications before they experienced gemcitabine-related myocardial ischemia [17,18]. In another patient with a previous episode of gemcitabine-induced myocardial ischemia, the next gemcitabine infusion was started concomitantly with IV nitroglycerine and beta blockers [19].…”
Section: Discussionmentioning
confidence: 99%
“…This side effect is likely because of a gemcitabine metabolite, 2′,2′‐difluorodeoxyuridine (diFdU), which has a an equivalent half‐life of approximately 18–24 h similar to the time of onset of atrial fibrillation 8, 9. Several case reports have demonstrated acute myocardial infarction acutely post‐gemcitabine infection secondary to drug‐induced vascular injury or endothelial damage 10, 11, 12…”
Section: Discussionmentioning
confidence: 99%
“…Bdair et al [10] reported a case with previous myocardial infarction history, which developed AMI 3 days after gemcitabine therapy. Our subject, who had a history of coronary artery disease, developed chest pain with accompanying newly developed LBBB shortly after drug infusion, but no biomarker increases were observed and both symptoms and LBBB resolved with antianginal treatment.…”
Section: Discussionmentioning
confidence: 99%